Distribution of Non Volant Small Mammals in Different Landscape in Universiti Tun Hussein Onn Malaysia, Johor - Mohd Shaifuddin, Hani Fasihah; Sapaat, Arney (Enhanced Knowledge in Sciences and Technology, 2026)
The distribution of non volant small mammals was investigated across different landscape areas within Universiti Tun Hussein Onn Malaysia (UTHM), Johor. This study aimed to (1) catalogue the variety of non volant small mammal species present in the study area and (2) assess how different habitat types influence their distribution and abundance. Field sampling was conducted between August and November 2025 using ground level live trapping and direct observation across three habitat types: agricultural monoculture area (oil palm), disturbed area (lake edge), and coastal area. A total of eight non volant small mammal species were recorded through direct live trapping, comprising 41 individuals, while additional species were documented through direct observation. The captured assemblages were dominated by generalist rodent species, particularly Rattus rattus, Rattus exulans, and Rattus tiomanicus. Forest associated species such as Maxomys rajah and Maxomys whiteheadi were recorded in low number, indicating limited suitability of highly modified habitats for disturbance sensitive taxa. Observational records revealed the presence of arboreal species including Tupaia glis, Callosciurus notatus, and Ratufa bicolor, which were not effectively sampled by ground level live traps. Species richness and distribution varied among habitat types. The disturbed lake edge habitat supported the highest species richness and diversity. In contrast, the agricultural monoculture area exhibited lower diversity with strong dominance by generalist to overall species presence. The Shannon-Wiener diversity index indicated moderate species diversity with uneven species distribution across habitats. Overall, the findings demonstrate that habitat type and structural complexity play important roles in shaping non volant small mammal communities. This study provides essential baseline data for future ecological research and highlights the importance of integrating multiple sampling approaches when assessing small mammal assemblages in human modified landscapes.